Kebijakan Perlindungan Anak: (Mengulas UU Nomor 35 Tahun 2014 Pasal 9 Ayat 1) - Junaidi; Khoiruman (LPPI Universitas Al-Qolam Malang, 2023)
In the world of education itself, the culture of punishing children who are addictive is very common, although we all don't know what effect it will have on children after receiving the punishment. children's rights, so that there are no misunderstandings about child protection and their rights. The author also hopes that the government will socialize the contents of the socially just child protection policy, so that all levels of society can better understand the contents of the policy, and the authors really hope that all levels of society will play a role. Key words: children; laws; policy; protection; rights